CLARIFY 2021: explanation and elaboration of the Delphi-based guidelines for the reporting of yoga research - Holger Cramer; Lesley Ward; Steffany Moonaz; Daryl Nault (BMJ Open)
Background Reporting of yoga research often lacks the detail required for clinical application, study replication, summary research and comparative effectiveness studies.Methods To improve the transparency of reporting yoga interventions, and building on the development of previous reporting guidelines, a group of international yoga research stakeholders developed the consensus-based CheckList stAndardising the Reporting of Interventions For Yoga (CLARIFY) guidelines.Results The 21-item CLARIFY checklist outlines the minimum details considered necessary for high-quality reporting of yoga research. This paper provides a detailed explanation of each of the 21 items of the CLARIFY checklist, together with model examples of how to integrate each item into publications of yoga research. The CLARIFY guideline serves as an extension for existing research reporting guidelines, and is flexible for use across all study designs.Conclusion We strongly encourage the uptake of these reporting guidelines by researchers and journals, to facilitate improvements in the transparency and utility of yoga research.